Bolečina v zapestju - Antolič, Vane (Medicinski razgledi, 1999)
In the article the pain in the wrist from the standpoint of view of the general practitioner is presented. The article deals with diseases of the wrist which can be treated by general practitioner. Some relevant details regarding the medical history and orthopaedic examination are presented helping the general practitioner in his decision regarding the fereral to the specialist. The information in the article should be regarded more as recommendation; the general practitioner should take into account also other circumstances which can influence the outcome (his experience, time and equipment).
Keywords: Wrist; zapestje; Wrist joint; bolečina; Biomechanics; poškodbe; Pain; biomehanika; artritis; Diagnosis; Etiology; Carpal tunnel syndrome; Tendinitis; Arthritis; Tendon injuries